Comprehensive analyses of DNA methylation of the TIMP3 promoter in placentas from early-onset and late-onset preeclampsia - Cruz, Juliana de O.; Conceição, Izabela M.C.A.; Sandrim, Valeria C. [UNESP]; Luizon, Marcelo R. (Elsevier, 2022)
Preeclampsia (PE) is classified into late-onset (LOPE) or early-onset (EOPE) according to gestational age of onset (≥34 or <34 weeks, respectively), and into preterm and term (delivery at <37 or ≥37 weeks, respectively). An imbalanced expression of matrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs) impairs proper placentation in PE, and DNA methylation (DNAm) may affect their expression. We performed comprehensive analyses of DNAm and TIMP3 expression in placentas from PE reclassified into EOPE, LOPE, and term PE. We identified significant differentially methylated probes at the TIMP3 promoter in PE (28), EOPE (38), LOPE (20), and term PE (4) compared to controls, and in EOPE vs. LOPE (8). Moreover, we found a hypomethylation >70% in all groups (except EOPE vs. LOPE) and an increased TIMP3 expression in corresponding placental samples from PE, EOPE and LOPE compared to controls (p<0.05). Our findings highlight the role of DNAm of the TIMP3 promoter region regarding an epigenetic mechanism in PE.
Keywords: DNA methylation; Early-onset pre-eclampsia; Epigenomics; Late-onset pre-eclampsia; Pre-eclampsia; Tissue inhibitor of Metalloproteinase-3